2006
DOI: 10.1080/07373930600558979
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of Withering Characteristics of Tea Leaves

Abstract: The withering characteristics of tea leaves were examined for different temperatures. Tea leaves were withered at a temperature range of 20-45 C with a constant air velocity of 1.1 m/s. The experimental results illustrated the absence of constant-rate drying period and withering took place only in the falling-rate period. During the falling-rate period, at constant drying air flow rate, the drying rate increased and drying time decreased with the increase in drying air temperature. Drying models of Henderson a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 20 publications
(34 reference statements)
5
33
0
2
Order By: Relevance
“…The constant rate drying period was not observed owing to very high initial water content and drying took place in the falling rate period. This result was in agreement with previous studies on drying of foods (Akpinar et al 2004;Ghodake et al 2006;Singh et al 2006;Kaya et al 2007;Sobukola et al 2007). It showed that diffusion was the most likely physical mechanism governing moisture movement in aonla shreds.…”
Section: Drying Characteristics Of Aonla Shredssupporting
confidence: 83%
“…The constant rate drying period was not observed owing to very high initial water content and drying took place in the falling rate period. This result was in agreement with previous studies on drying of foods (Akpinar et al 2004;Ghodake et al 2006;Singh et al 2006;Kaya et al 2007;Sobukola et al 2007). It showed that diffusion was the most likely physical mechanism governing moisture movement in aonla shreds.…”
Section: Drying Characteristics Of Aonla Shredssupporting
confidence: 83%
“…Withering is one of the processed requiring the most space . The freshly harvested leaves are conditioned physically and chemically for the next operation (maceration or rolling) (Ghodake et al, 2006). During this period, the shoots partially loose moisture with moisture levels dropping from approximately 70-80% to 60-70% (wet basis), and the turgid shoots become flaccid.…”
Section: Withering Processmentioning
confidence: 99%
“…Entre las diferentes investigaciones se puede destacar: Ozcan et al, (2005); Roberts et al, (2008); Ghodake et al, (2006); Karathanos (1999); Xanthopoulos et al, (2007); Wang et al, (2007) …”
Section: Modelos Empíricosunclassified
“…Rocha (2012) utilizó diferentes modelos empíricos para estudiar la cinética del secado de tomillo a temperaturas de 30, 40, 50, 60 y 70 ºC a una velocidad de 1 m/s. Para el cálculo de la difusividad efectiva uso un modelo de lámina infinita en una hoja obteniendo valores entre 3.69 x 10 -12 y 1.19 x 10 -10 m Existen otras investigaciones sobre la modelación matemática y sobre el estudio de las cinéticas de secado para diversas hortalizas y plantas medicinales, como la albahaca (Ozcan et al 2005), plantas aromáticas , hojas de acelga (Alibas 2006), hojas de té (Ghodake et al 2006), Rehmannia (Rhim et al, 2007), hojas de romero , cebolla (Lee & Kim 2008) y Berberis (Aghbashlo et al 2009). …”
Section: Secado De Tomillounclassified
See 1 more Smart Citation